Planning, execution, and revision in mathematics problem solving: Does the order of the phases matter?. (June 2019) - García, Trinidad; Boom, Jan; Kroesbergen, Evelyn H.; Núñez, José Carlos; Rodríguez, Celestino
Highlights: Elementary students solving problem process is more linear than recursive. The uses of planning strategies before execution are related to good performance. The use of revision strategies after execution are related to good performance. Hierarchical resolution process related to students' judgments of success. Abstract: The present study analysed the mathematical problem-solving processes, in terms of linearity and recursion, and the relationship with actual and self-perceived performances of a sample of 524 students of upper elementary students. The results showed a more linear than recursive process while performing the tasks, mainly characterized by continuity. The use of planning strategies before execution and the use of revision strategies after this phase were both significantly related to good performance, even if rates of success were low. The presence of a linear and hierarchical resolution process was related to students' judgments of success, while recursion, or going back in the process, was associated with judgments of failure. Results are discussed in the light of current research on mathematics problem-solving.